2018
DOI: 10.3390/en11112882
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water–Oil Saturation on the Fracture Process Zone: A Modified Dugdale–Barenblatt Model

Abstract: The wetting and nonwetting fluid saturations in porous reservoirs always change during long-term injection and production. The fracture process zone (FPZ) is a prominent feature in the rock fracture process. If the FPZ properties are influenced by pore fluids, the process of hydraulic fracturing will change greatly. The existing models do not consider the role of pore fluid when characterizing the FPZ. In this paper, a modified Dugdale–Barenblatt (D–B) model with capillary pressure is proposed. The model refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The pore fluid also influences the size of rock FPZ. Nie et al [181] found in the experiment that the rock FPZ is affected by the fluid in the pores. The FPZ of the watersaturated specimen is 30% longer than that of the dry specimen, and the capillary force can reduce the FPZ length.…”
Section: Fracture Process Zonementioning
confidence: 99%
“…The pore fluid also influences the size of rock FPZ. Nie et al [181] found in the experiment that the rock FPZ is affected by the fluid in the pores. The FPZ of the watersaturated specimen is 30% longer than that of the dry specimen, and the capillary force can reduce the FPZ length.…”
Section: Fracture Process Zonementioning
confidence: 99%
“…The digital image correlation method was used to monitor the fracture process in real time, and the displacements of the specimens were calculated by an open-source program [47]. Based on the existing methods, the fracture process zone length of reservoir rocks was identified by the characteristics of horizontal displacement [48][49][50]. And the typical fracture process zone lengths of Lucaogou Formation rocks with different brittleness B 4 were characterized in Figure 11, where the length of the fracture process zone is larger when the rock brittleness evaluated by the improvement model is smaller.…”
Section: The Length Of Fracture Process Zone In Different Brittlementioning
confidence: 99%
“…Distilled water and saline solution of KCl caused a 70% decrease, the decrease with alcohol and kerosene was 25%. Different authors have indirectly measured that the size of the FPZ is larger for samples saturated in certain aqueous solutions [42,68]. At the same time, the importance of FPZ (r c .)…”
Section: How Interaction Between Defects and Fluids Affects Fracture Toughnessmentioning
confidence: 99%
“…A key to further reduce scatter and uncertainty in fracture testing of shale rocks is therefore to ensure a similar initial microcrack density. References in the literatur [42,68,70] point to two basic techniques: ultrasound measurements and micro-tomography. Propagation speeds of mechanical waves are modified by matrix stiffness; detection thresholds may be the key in the applicability of tomography techniques.…”
Section: How Interaction Between Defects and Fluids Affects Fracture Toughnessmentioning
confidence: 99%